2012
DOI: 10.1002/cncy.21244
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tumor markers in cytological fluid obtained from computed tomography–guided needle aspiration biopsies for the diagnosis of ground‐glass opacity pulmonary lesions

Abstract: BACKGROUND:The purpose of this study was to assess whether analyses of tumor markers in cytological fluid can improve the performance of computed tomography (CT)‐guided needle aspiration biopsy (NAB) for the diagnosis of ground‐glass opacity (GGO) pulmonary lesions.METHODS:Forty‐two patients were prospectively enrolled for CT‐guided NAB. Levels of cytokeratin 19 fragments (CYFRA 21‐1) and carcinoembryonic antigen (CEA) from serum and cytological fluid were measured. The cutoff values of 3.3 ng/mL for CYFRA 21‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The SROC curve presented an overall summary of SEN and SPE, with an AUC of 0.97, also indicating a high overall accuracy. This result was similar to the article published in 2014, in which the SEN was in the range of 0.71–0.97 (pooled 0.92; 95% CI = 0.88–0.95), while SPE was in the range of 0.80–0.97 (pooled 0.94; 95% CI = 0.84–0.98) (16), and more related original studies that expanded the sample size have been included in our study (7,9–15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SROC curve presented an overall summary of SEN and SPE, with an AUC of 0.97, also indicating a high overall accuracy. This result was similar to the article published in 2014, in which the SEN was in the range of 0.71–0.97 (pooled 0.92; 95% CI = 0.88–0.95), while SPE was in the range of 0.80–0.97 (pooled 0.94; 95% CI = 0.84–0.98) (16), and more related original studies that expanded the sample size have been included in our study (7,9–15).…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided percutaneous lung biopsy is an effective diagnostic technique to make certain of the nature of pulmonary lesions (1). Previous studies have reported that the diagnostic accuracy of CT-guided puncture biopsy for GGNs is in the range of 78.6%-100.0%, which fluctuates widely (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In addition, the sample size of each study varies, and the results of studies with small sample sizes were not convincing.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in their presence or levels [9,10] can indicate the presence of tumors, playing a crucial role in lung cancer screening, diagnosis, and treatment assessment. Nevertheless, the ability of tumor markers to detect early-stage lung cancer is not optimal, as indicated by the sensitivity rates reported in studies [11,12]. Additionally, no individual serum tumor marker is exclusively reliable for lung cancer detection [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the sensitivity of tumor markers in patients with early lung cancer is inferiority. 8 Moreover, no single serum tumor marker can be specifically used to detect lung cancer. 9,10 To improve the early diagnosis rate of lung cancer, it is a research hotspot to combine the conventional biological indicators and tumor markers in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%